2018
DOI: 10.1186/s12974-018-1233-2
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effect of LPS on the expression of GPR81 lactate receptor in blood-brain barrier model in vitro

Abstract: BackgroundLipopolysaccharide (LPS) is one of the main constituents of the cell wall of gram-negative bacteria. As an endotoxin, LPS induces neuroinflammation, which is associated with the blood-brain barrier impairment. Lactate is a metabolite with some significant physiological functions within the neurovascular unit/blood-brain barrier (BBB). Accumulation of extracellular and cerebrospinal fluid lactate is a specific feature of bacterial meningitis. However, the role of lactate production, transport, and sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 40 publications
0
34
0
2
Order By: Relevance
“…Lipopolysaccharide (LPS) is a compound of the cellular wall of Gram-negative bacteria [17]. Previous studies demonstrated that LPS-caused podocyte damage could be used as an in vitro cell model of proteinuria to analyze the pathogenesis of NS and testing new medicine for NS [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) is a compound of the cellular wall of Gram-negative bacteria [17]. Previous studies demonstrated that LPS-caused podocyte damage could be used as an in vitro cell model of proteinuria to analyze the pathogenesis of NS and testing new medicine for NS [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Ранее нами были выявлены подобные изменения рецепции и транспорта лактата в модели бактериального воспаления гематоэнцефалического барьера in vitro [14].…”
Section: Discussionunclassified
“…The mechanism of GPR81-mediated inflammation impaired endothelial layer weakens the ability of sensing or transporting lactate, in consequence, MCT1 and GPR81 expression is reduced (Boitsova et al, 2018). In vivo, the decreased expression of GPR81 is also observed in the mouse glaucoma model.…”
Section: Ameliorating Retinal Neuroinflammationmentioning
confidence: 99%